EFEK MODERASI KOMPENSASI PADA PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Danuji, Sahid -; Rahadhini, MD - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT The objective of this research is to analyze (1) effect of the motivation to employee performance; (2) effect of the job satisfaction to employee performance; (3) effect of the compensation to employee performance; (4) the role of compensation as a moderator of the effect motivation to employee performance; (5) the role of compensation as a moderator of the effect job satisfaction to employee performance. This research uses population research while the population is all employees in KSP Ben Silatu Grobogan consist of 33 respondents. Data collecting with questionaire technique through validity and reliability test. The analyze data use the multiple regression analysis and moderated regression analysis through standardized residual method, and previously the researcher uses classical assumption test. The hypothesis test uses t test. The analysis results which could be reported are the questionaire of all variables are valid and the reliable. The result of classical assumption test show that the model is no multicoliniearity, no heteroskedasticity, no autocorrelation and the residual is normal. Results of t test indicate that: (1) motivation has a significantly effect to employee performance. This is indicated by t test with p value (0,003) < 0,05 thus supporting hypothesis 1; (2) job satisfaction has significantly effect to employee performance. This is indicated by t test with p value (0,016) < 0,05 thus supporting hypothesis 2; (3) compensation has significantly effect to employee performance. This is indicated by t test with p value (0,011) < 0,05 thus supporting hypothesis 3; (4) compensation has moderate the effect of motivation to employee performance. This is indicated by t test with p value (0,009) < 0,05 thus supporting hypothesis 4; (5) compensation has moderate the effect of job satisfaction to employee performance. This is indicated by t test with p value (0,047) > 0,05 thus supporting hypothesis 5. Keywords: compensation, job satisfaction, motivation, employee performance